A Case Report on Hirayama Disease - Sharma, B. B.; Sharma, Shashi; Sarin, Monu; Bhutani, Abhivind; Lathwal, Surabhi (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Hirayama Disease is a non-progressive juvenile spinal muscular atrophy of the distal upper limb, Cervical myelopathy affects the dorsal aspect of the cervical cord as a result of the flexion action. It's a benign motor neuron condition with a gradual course that eventually remains stagnant. Magnetic resonance imaging in flexion is quite sensitive to these results, which may be missed in neutral position. Hirayama disease characteristically affects adolescents and young adults and presents as weakness and atrophy of the distal part of the upper limbs. We discuss a case of an adolescent boy who came with asymmetrical weakness in both hands, and whose magnetic resonance (MR) imaging in flexion indicated Hirayama disease-like alterations.